Comparisons of bone density and body composition among adolescents with anorexia nervosa and atypical anorexia nervosa. Issue 5 (16th February 2019) - Nagata, Jason M.; Carlson, Jennifer L.; Golden, Neville H.; Long, Jin; Murray, Stuart B.; Peebles, Rebecka
Abstract: Objective: To compare bone mineral density (BMD) and body composition among adolescents: (a) with atypical anorexia nervosa (AAN) versus anorexia nervosa (AN) and (b) those with and without a prior history of overweight. Method: Electronic medical records of patients 9–20 years with AN or AAN who underwent dual ‐ energy x‐ray absorptiometry scans were retrospectively reviewed and analyzed. Results: A total of 286 adolescents with AN or AAN were included. In linear regression models, AAN was associated with greater Z ‐scores in whole body bone mineral content (BMC, B = 0.88, p < 0.001), lumbar spine BMD ( B = 0.79, p = 0.002), femoral neck BMD ( B = 0.670, p = 0.009); fat mass index ( B = 1.33, p = 0.003), and lean body mass index ( LBMI, B = 1.10, p < 0.001) compared to AN, adjusting for age, sex, and duration of illness. A prior overweight history was associated with greater Z ‐scores in whole body BMC; lumbar spine BMD, total hip BMD, femoral neck BMD, and LBMI. Discussion: Adolescents with AAN had higher BMD Z ‐scores than adolescents with AN; adolescents with a prior overweight history had greater BMD Z ‐scores than adolescents without a prior overweight history. These findings may inform clinical guidelines for the medical management of AAN.